Identificación de variables Socioeconómica de los Tecnólogos en la continuidad de su formación profesional - Banguero-Lozano, Harold Enrique; Franco-Cortes, Maria del Pilar; Romero-Olmedo, Gustavo Alfonso (Revista Científica, 2016)
The main objective of this study is to keep track to technologists who expressed their desire to continue their professional cycle, regardless if the process is carried out in the same institution or in a different one. To accomplish this, it´s necessary some data from the Ministry of Education, the Observatory of the Colombian University, the National Observatory for Education and primary universities in Cali which offer technology programs. This research process was developed through the Human Capital Theory, social analysis, statistics and econometrics, in order to analyze one of the educational components of professionalization, taking as a starting point the technology formation and preferences or needs of students graduating in technology.